The Design and Implementation of a Professional Development Program for Physician Assistants in an Academic Emergency Department. Issue 2 (12th September 2019) - Monette, Derek L.; Baccari, Brian; Paskind, Laura; Reisman, David; Temin, Elizabeth S.
Abstract: Physician assistants (PAs) are expanding their role in academic emergency departments (EDs). There are no published models for how to integrate PAs into departmental educational activities, scholarship, and operations outside of a PA residency approach. We created a professional development program for PAs that would provide them with opportunities to integrate into all aspects of our department mission and provide them with a forum for personal growth and ongoing education. The program provides PAs with resources including protected time and mentorship to become a content expert in an academic area of interest. We review our 5‐year experience creating and implementing this program, which has grown from six PAs in 2013 to 24 PAs in 2018. These PAs now have formal roles in five of our eight divisions, participating in education, administrative, and research activities. The retention rate for PAs in this program is 90.2% versus 85.7% for PAs at our department who are not in the program. Our experience and results demonstrate the value of investing in the professional development and continued education of PAs at an academic ED versus the traditional model of service and the potential for integration into all aspects of an academic ED's mission.